Inequalities in Oral Health for Children with Disabilities: A French National Survey in Special Schools - Hennequin, Martine (Public Library of Science, 2008)
BACKGROUND: Despite wide recognition that children with disability often have poor oral health, few high quality, controlled results are available. METHOD: Twenty-four objective and subjective criteria covering feeding, autonomy, access to dental care, oral hygiene, oral disease, general health and behavior were evaluated in a observational cross-sectional study of 2,487 children with disability (DC group), 4,772 adolescents with disability (DA group) and 1,641 children without disability (NDC group). Five algorithms ranked the subjects according to clinical criteria in three original oral health indices: the Clinical Oral Health Index (COHI), indicating the level of oral health problems, the Clinical Oral Care Needs Index (COCNI) giving dental care need levels, and the Clinical Oral Prevention Index (COPI) determining possible needs in terms of dental education initiatives. RESULTS: DC-group children presented poorer oral health and had greater needs in both treatment and preventive oral health actions than NDC-group children (OR = 3.97, 95% CI = 3.25–4.86 for COHI; OR = 2.01, 95% CI = 1.77–2.28 for COCNI; OR = 5.25, 95% CI = 4.55–6.02 for COPI). These conditions were worse again in the DA group comparing to the DC group (OR = 3.52, 95% CI = 2.7–4.6 for COHI; OR = 1.52, 95% CI = 1.38–1.69 for COCNI; OR = 1.53, 95% CI = 1.39–1.69 for COPI). CONCLUSION: Clinical indices generated by algorithmic association of various clinical indicators allow sensitive clinical measurement, and in this study demonstrated inequalities in oral health for children with disabilities schooling in institutions. Questions need now to be addressed as to the measures that could be taken to compensate for this situation.